Analisis Stabilitas Jangka Pendek dan Jangka Panjang Timbunan Tanah Lunak Menggunakan Tipe Drainase Undrained A dan Undrained B Pada Metode Elemen Hingga Plaxis 2D - Edward Widjaja (Syntax Idea)
One of the methods of soil improvement in the case of highway embankments is to perform pre-loading to increase the shear strength of the subgrade. In this study, the embankment case is modeled in PLAXIS 2D software. The analysis will be conducted under short-term, long-term embankment conditions, services, and pseudostatic earthquakes. The study was conducted by modeling the subgrade using the effective stress analysis (ESA) approach with two different drainage types, Undrained A and Undrained B. In the model with Undrained A drainage type, the long-term stability analysis was performed by modeling consolidation, while the long-term analysis with Undrained B drainage type was performed by updating the undrained shear strength of the subgrade based on the equation by Han (2015). The analysis results show that the factor of safety values of Undrained drainage type A are about 10-28% greater than those of Undrained drainage type B throughout the preloading, service, and earthquake conditions. The difference in the factor of safety values occurs due to differences in the definition of safety factor and failure criterion. Stability analysis with Undrained A drainage type needs to be conducted carefully by considering the accuracy of the long-term parameters, while the accuracy of stability analysis with Undrained B can be improved by calibrating the coefficients in Han, Jie (2015) equation based on the undrained friction angle obtained from the CU triaxial test.